Analyzing the determinants of individual action on climate change by specifying the roles of six values in South Korea - Kwon, Seol A.; Kim, Seoyong; Lee, Jae Eun (Sustainability (Switzerland), 2019)
The serious problems stemming from climate change require an active response it. This study focuses on the role of value factors in action on climate change. Individuals' values systematically influence the fundamental orientation of their attitudes and behaviors. Therefore, this study analyzes whether six values, namely: ideology, environmental justice, religiosity, personal norms, scientific optimism, and environmentalism, influence action on climate change directly or indirectly, and compares their effects with perception factors' impact. The results indicate that religiosity decreased action on climate change, whereas personal norms, science and technology (S & T) optimism, and environmentalism increased such action. Among the perception factors, perceived risks and benefits, trust, and knowledge increased action on climate change. Furthermore, perception factors explained action on climate change more than value factors did. Moreover, value factors (i.e., S & T optimism and environmentalism) moderated the impacts of perceived risks, perceived benefits, and negative emotions on action against climate change.
Keywords: Action on climate change; Emotion; Environmental justice; Environmentalism; Ideology; Knowledge; Perceived risk and benefit; Perception; Personal norm; Religiosity; Science and technology optimism; Trust; Value